1990
DOI: 10.1063/1.102530
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence characteristics of AlGaN-GaN-AlGaN quantum wells

Abstract: AlxGa1−xN-GaN quantum wells were grown on basal plane sapphire by low-pressure metalorganic vapor deposition. The photoluminescence spectra of samples of different well thicknesses and x values were measured. The experimental data were compared with the calculated solutions of the finite square quantum well and the bound states involved in the optical transition were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(27 citation statements)
references
References 6 publications
1
26
0
Order By: Relevance
“…In Al x Ga 1Àx N, the band gap increases from 3.4 to 6.2 eV, 22 about 65% of the band gap difference is accommodated in the conduction band (up shift) and 35% in the valence band (down shift). 23 Thus, an Al-content of around x ¼ 0.2 will be sufficient to align the conduction bands in Cu 2 O and Al x Ga 1Àx N. For such small Al-contents, the electrical properties of the films are still excellent and easily controllable. 24 For Cu 2 O on ZnO, the conduction band offset is 0.97 eV.…”
mentioning
confidence: 99%
“…In Al x Ga 1Àx N, the band gap increases from 3.4 to 6.2 eV, 22 about 65% of the band gap difference is accommodated in the conduction band (up shift) and 35% in the valence band (down shift). 23 Thus, an Al-content of around x ¼ 0.2 will be sufficient to align the conduction bands in Cu 2 O and Al x Ga 1Àx N. For such small Al-contents, the electrical properties of the films are still excellent and easily controllable. 24 For Cu 2 O on ZnO, the conduction band offset is 0.97 eV.…”
mentioning
confidence: 99%
“…3,4 Quantum wells ͑QWs͒ have been the device structure of choice for efficient III-nitride semiconductor based light emitters. 5,6 Conventional nitride c-plane multiple QW structures generate fixed sheet charges at the interfaces due to the spontaneous and piezoelectric polarization. [7][8][9][10] which induce internal electric fields, lead to carrier separation, and reduce the radiative recombination rate.…”
mentioning
confidence: 99%
“…Values as high as 1500 cm2/Vs at room temperature have been achieved in the authors' laboratory (Wu, et al 1996). The optical properties of AlGaN/GaN quantum wells (Kahn, et al 1990) were found to be determined by both, quantum and strain related effects Krishnankutty, et al 1992b). MOCVD A1N films showed a full width of half maximum of the (002) x-ray rocking curve peak as low as 97 arcseconds (Saxler, et al 1994).…”
Section: Growth Of Algan and Algan/gan Heterostructuresmentioning
confidence: 99%